Peran Edukasi terhadap Peningkatan Pengetahuan dan Perubahan Sikap Anggota Majelis Taklim Halimatussa'diyah tentang Tanaman Obat Keluarga - Jumasni Adnan; Putri Juanti; Aulia Insani Latif; Nurhalisa Ahwal; Gina Shabarina Sahar (Jurnal Mandala Pengabdian Masyarakat, 2026)
Majelis taklim as a non-formal Islamic educational institution, serves as an effective medium to enhance individual knowledge and skills due to its flexible structure, efficiency, and rapid outcomes. Its presence is increasingly important and expected to play a greater role in addressing community issues, particularly in promoting family health through the utilization of Family Medicinal Plants (TOGA). TOGA are household-cultivated plants with medicinal properties that support disease prevention and health maintenance. However, their utilization among women in majelis taklim remains limited, largely due to insufficient knowledge and the prevailing reliance on synthetic medicines. Enhancing public knowledge is therefore essential, as it can influence attitudes toward the use of natural remedies. This study aimed to examine the role of education in improving knowledge and community attitudes to TOGA. A quasi-experimental method with one-group pretest–posttest design, with 44 respondents. The results showed that a significant improvement in both knowledge and attitudes following the educational intervention, with a p-value of 0.000. It could be concluded that educational on TOGA effectively enhance knowledge and foster positive changes in community attitudes to the use of Family Medicinal Plants